Energetic Proton Acceleration Associated With Io's Footprint Tail. Issue 24 (23rd December 2020) - Clark, G.; Mauk, B. H.; Kollmann, P.; Szalay, J. R.; Sulaiman, A. H.; Gershman, D. J.; Saur, J.; Janser, S.; Garcia‐Sage, K.; Greathouse, T.; Paranicas, C.; Allegrini, F.; et al.
Abstract: Observations of energetic charged particles associated with Io's footprint (IFP) tail, and likely within or very near the Main Alfvén Wing, during Juno's 12th perijove (PJ) crossing show evidence of intense proton acceleration by wave‐particle heating. Measurements made by Juno/JEDI reveal proton characteristics that include pitch angle distributions concentrated along the upward loss cone, broad energy distributions that span 50 keV to 1 MeV, highly structured temporal/spatial variations in the particle intensities, and energy fluxes as high as 100 mW/m 2 . Simultaneous measurements of the plasma waves and magnetic field suggest the presence of ion cyclotron waves and transverse Alfvénic fluctuations. We interpret the proton observations as upgoing conics likely accelerated via resonant interactions with ion cyclotron waves. These observations represent the first measurements of ion conics associated with moon‐magnetosphere interactions, suggesting energetic ion acceleration plays a more important role in the IFP tail region than previously considered. Plain Language Summary: NASA's Juno spacecraft orbits Jupiter's polar region and makes direct measurements of the fields and particles that are responsible for creating Jupiter's powerful auroras. In this article, we present new observations that show intense proton acceleration occurring at altitudes near the auroral emissions created by the interaction between Jupiter's moon Io and the surrounding plasma and magnetic field environment. These unique observations provide clues on how particles are being accelerated and will help constrain particle acceleration theories. Key Points: Juno's likely crossing of Io's Main Alfvén Wing (MAW) during PJ12 reveals evidence of transverse ion acceleration Observations suggest wave‐particle interactions with ion cyclotron waves as the favored acceleration mechanism; however, Alfvén acceleration was not ruled out Ion conics generated in Io's footprint tail or near the MAW are more intense and energetic than observed in other auroral regions